Vaccinology : Principles and Practice. - Morrow, W. John W. (John Wiley & Sons, 2012)
Covering all aspects of vaccine research and development in one volume, this authoritative resource takes a comprehensive and systematic approach to the science of vaccinology focusing not only on basic science, but also on the many stages required to commercialize and navigate the regulatory requirements for human application, both in the United States and Europe. Reviews in detail the process of designing a vaccine, from the initial stages of antigen discovery to human applicationIncludes evaluation of vaccine efficacy and safetyDetails clinical trial design, including regulatory requirements.